دافعية استخدام التعلم التعاوني لتنمية تعليم مهارة الكلام - Ahmad Taufiq (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2018)
Language is basically speech, but writing is an attempt to represent speech. It is proven that man knows speech before writing long time ago. Writing emerged in a later period of human history. The child learns to speak before he can learn to write, which he begins to learn when he enters school. All good people speak their mother tongues fluently and there are many people do not know how to write in their own languages. There are some languages still spoken in unwritten way. Cooperative learning is not where students who work together to achieve their goals unless they cooperate with each other. The mere distribution of students to groups and informing them to work together does not fall under the name of cooperative learning, even if these are the most important features and main features, there is a wide difference between the distribution of students on groups to work, and the consolidation of the concept of cooperation and rooted in the minds of students with special needs.